ANALISIS KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAH DESA DAERAH PROVINSI SULAWESI TENGAH - Haidir, Haidir (Katalogis, 2013)
The purpose of the study was to analyze the performance the Civil Servants Agency Office of Rural Community Empowerment and the Provincial Government of Central Sulawesi and the factors that hinder the performance of the Civil Service Agency Office of Rural Community Empowerment and the Provincial Government of Central Sulawesi. The population in this study was 58 all employees, samples selected employees 20 people with the sampling technique using purposive sampling. Data collection techniques in this study using the method: Observation (observation), interviews and documentation. The analysis technique used is qualitative analysis Dwiyanto’s theory. The results showed that the performance of the Civil Service Agency Office of Rural Community Empowerment and Local Governments of Central Sulawesi province can be seen to the indicators of Quality of Service, Responsiveness, Responsibility, Productivity and Accountability mostly well executed nonetheless still has shortcomings. The factors inhibiting the performance of the Civil Service Agency Office of Rural Community Empowerment and Local Governments of Central Sulawesi province is human resources, incentives and discipline.